“I’ve Never Told Anyone”: A Qualitative Analysis of Interviews With College Women Who Experienced Sexual Assault and Remained Silent - Caron, Sandra L. (Violence against women, 2022)
The purpose of this study was to gain an understanding of the decision made by some college women who are raped to tell no one. In-depth interviews were conducted with 15 college women between the ages of 19-24 who had never shared their sexual assault with anyone prior to speaking to the researchers. This study provides a systematic investigation of the factors underlying women’s decisions to remain silent. The knowledge and understanding gained from these in-depth interviews offer insight for individuals and institutions to support these students and for the development of future efforts encouraging women survivors to tell someone.